Study of the Porosity Based on Structurally Inhomogeneous Materials Al-Ti - Заболотний, Олег Васильович; Ilchuk, Nataliia; Гульчук, Юрій Миколайович (Springer International Publishing, 2021)
A technology for forming structurally inhomogeneous materials of Al-Ti samples has been developed. The components of the initial mixture were calculated based on the bulk of real powders, taking into account the mass, stoichiometric coefficients of the original components, the purity, and the bulk density. The microstructure of structurally inhomogeneous materials samples was studied using application programs. Besides, image recognition is performed at various magnifications before etching and after etching. The main properties of Al-Ti materials at different temperatures are obtained. An interpolation of the porosity dependence is constructed based on theoretical and experimental data. It is proved that the granulometric composition of structurally inhomogeneous materials has been improved based on the correct percentage of the initial mixture. The dependences of porosity on pressure and melting temperature for manufacturing structural parts are substantiated and constructed. Thus, there is reason to argue that improving the granulometric composition of Al-Ti based on a correctly selected percentage of the initial mixture, taking into account the further process of forming structurally inhomogeneous materials, allows to control such a parameter as porosity, as well as to study the physical and mechanical properties in the manufacture of various structural purposes parts to predict their structures.
Keywords: Technology of sample formation; Microstructure; Components of the initial mixture; Percentage ratio; Powder filling; Temperature; Pressing pressure; Physic-Mechanical properties; Particle size distribution